Meredam Epidemi Burnout di Kalangan ASN : Strategi Kebijakan Berbasis Penguatan Ketahanan Organisasi - Pratiwi, Anik (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The phenomenon of burnout among the State Civil Apparatus (ASN) in Indonesia has evolved into a systemic problem threatening the quality of governance. However, to date, no comprehensive national strategy has specifically addressed its root causes. This policy paper aims to formulate alternative policies for managing burnout by focusing on strengthening organizational unit factors as the primary determinant. Employing a qualitative method with a descriptive analytical approach, this study synthesizes scholarly articles and policy documents over the 2020–2026 period. The findings indicate that organizational factors—including limited social support, inappropriate job design, weak reward systems, and minimal competency development—have a dominant influence (45.5 percent) and serve as the entry point for intervening in other factors. Based on Eugene Bardach’s feasibility criteria, four priority policy alternatives were formulated: (1) Strengthening Social Support and Leadership, (2) Sustainable Competency Development, (3) Output-Based Flexible Working Arrangement, and (4) Real-Time Workload Rationalization. These four policy alternatives are not mutually exclusive and require phased implementation, with Strengthening Social Support and Leadership recommended as the foundational initiative to be prioritized first. These policies are expected to foster a productive yet humane working environment for ASN.